Evaluation of cholesterol lowering treatment of patients with familial hypercholesterolemia: a large cross-sectional study in The Netherlands - Pijlman, A.H.; Huijgen, R.; Verhagen, S.N.; Imholz, B.P.M.; Liem, A.H.; Kastelein, J.J.P.; Abbink, E.J.; Stalenhoef, A.F.H.; Visseren, F.L.J. (Atherosclerosis, 2010)
Heterozygous familial hypercholesterolemia (heFH) is a common autosomal dominant hereditary disorder caused by mutations in the LDL-receptor gene that lead to elevated plasma levels of low-density lipoprotein-cholesterol (LDL-c). Robust lowering of LDL-c levels is essential for risk reduction of premature cardiovascular diseases and early death. European and Dutch guidelines recommend to treat LDL-c to plasma levels <2.5mmol/l. In the present study we evaluated the treatment of heFH patients in The Netherlands. A cross-sectional study was conducted in outpatient lipid clinics of three Academic Centers and two regional hospitals. Patient records of known heFH patients were retrieved and data were reviewed on the use of lipid-lowering medication, plasma lipids and lipoproteins, safety laboratory results and reasons for not achieving treatment goals. The data of 1249 patients with heFH were available. Nearly all patients (96%) were on statin treatment. The treatment goal for LDL-c <2.5mmol/l was achieved in 261 (21%) patients. Among those who did not reach LDL-c goals, 261 (27%) were on combination therapy of maximum statin dose and ezetimibe. Main reason (32%) why patients did not use maximum therapy despite an LDL-c ≥2.5mmol/l, was acceptance of a higher target LDL-c level by the treating physician. An alternative treatment goal of >50% LDL-c reduction, as recommended in the NICE guidelines, was achieved in 47% of patients with an LDL-c ≥2.5mmol/l and not using maximum therapy. Only a small proportion of patients with heFH reaches the LDL-c treatment target of <2.5mmol/l. These results emphasize the need for better monitoring, better utilization of available medication and for new treatment options in heFH to further decrease LDL-c levels.